PRÁTICAS DE GOVERNANÇA CORPORATIVA EM FUNDO DE PENSÃO. ESTUDO DE UM CASO BRASILEIRO. - Caamaño, Paulo Castro (2008)
The following study investigates the Corporate Governance s practices used in pension funds and how it can indicate a better preservation of the unitholder interests to get future income. The theoretical referential that takes care of the ethics, the transparency, the agency theory and the main models and Corporate Governance s practices available in the world is analyzed in a restricted environment through the comparison between the theory and the business practice identified in case studies. The evidences noticed in the case study suggest that the Corporate Governance help in the minimization of the agency conflict between shareholders, managers and the unitholder, that due to their roll in the company, pay more attention in short term and long term respectively. The outcomes indicate that the Corporate Governance´s practices contribute to the preservation of the unitholder interests therefore they need to develop management tools that: increase the transparency of the company´s activities and its respective performance; clearly establish the responsibilities and the rules of the social agencies; improve the power structure to prior the segregation of functions among the departments and aid the investment management to the maintenance of the actuarial balance. The results still indicates that the main tools wich benefits the implantation of these practices were, externally, the Social Statute and internally the sector legislation.